Строговы: [романы] - Марков Георгий Мокеевич (Русская литература, 2021)
Экземпляры: (20220922) / Инвентарный номер: 63874 / Цена: 831.00 / Сис.шифр: Р2 / Авт.знак: М 26 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6